Basic and clinical science course 1996-1997. Section 12, Retina and vitreous (American Academy of Ophthalmology, 1996)
The textbook focuses on basic and clinical science, ophthalmology, and diseases of the retina and the vitreous. Intended for professional public and for university students.
Keywords: Vitreous Body; sklivec; oftalmologie; klinické lékařství; věda a výzkum; Clinical Medicine; věda; Retinal Diseases; Science; nemoci retiny; Ophthalmology